El arribo de personas a Loreto y el valor de la actividad económica de alojamiento y restaurantes periodo 2017 – 2021 - Paredes Vasquez, Veronica Vanessa (2025)
Loreto's economy depends largely on the extraction of natural resources such as oil and wood, negatively affecting the environment and depleting the non-renewable resource. Given this situation, tourism activity emerges as a viable alternative for the development of the region, rationally taking advantage of the multiple tourist attractions that nature offers. With this purpose, we seek to relate the arrival of people and the value generated by the economic activity of Loreto Accommodation and Restaurants during the period 2017 – 2021. Due to this, this quantitative research is carried out according to its nature, and correlational according to the explanation, counting for that with a Non-Experimental design. It is concluded that there is no relationship between the arrival of people and the economic activity of Accommodation and Restaurants, because the Correlation Coefficient is r = 0.391394745; and the Coefficient of Determination is R2 = 0.153189847. The trend of overnight stays and stay of people arriving in Loreto is variable throughout the period. Similarly, the installed capacity of lodging establishments had a positive evolution in the first years until 2019, then it was strongly affected by the COVID 19 pandemic in 2020. The Accommodation and Restaurants economic activity is the ninth in importance.